2016
DOI: 10.1590/2237-6089-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dependence and anxiety among benzodiazepine users in a provincial municipality in Rio Grande do Sul, Brazil

Abstract: Introduction: Benzodiazepines are among the most prescribed drugs for anxiety and one of the most used drug classes in the world and have a high potential for addiction. The objective of this study was to assess levels of dependence and anxiety among users of these drugs in the public health system. Methods: This was a cross-sectional, descriptive and quantitative study. Benzodiazepine users treated on the public health system were selected. Anxiety levels were assessed with the Hamilton Anxiety Scale and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
(15 reference statements)
0
12
1
4
Order By: Relevance
“…In the current study, the majority of the patients prescribed BZDs were adults aged 34 -60 years. [14] Interestingly, a study in Pakistan reviewing BZD use in outpatient clinics found the average age of BZD users to be 45 years, which is much younger than in our study. [18] Similarly, an SA study in 2004 reviewing BZD prescriptions from private healthcare patients found the mean age to be 43.17 years.…”
Section: Researchcontrasting
confidence: 67%
See 1 more Smart Citation
“…In the current study, the majority of the patients prescribed BZDs were adults aged 34 -60 years. [14] Interestingly, a study in Pakistan reviewing BZD use in outpatient clinics found the average age of BZD users to be 45 years, which is much younger than in our study. [18] Similarly, an SA study in 2004 reviewing BZD prescriptions from private healthcare patients found the mean age to be 43.17 years.…”
Section: Researchcontrasting
confidence: 67%
“…[13] Similarly, a study in Brazil's public healthcare sector assessing dependence and anxiety in BZD users also found clonazepam to be the most widely used BZD. [13,14] There are no studies on BZD utilisation from African countries other than SA. Notably, two of the four studies from SA also demonstrated that long-acting BZDs are most commonly used.…”
Section: Researchmentioning
confidence: 99%
“…Despite a high addiction potential, benzodiazepines are among the most prescribed drugs for anxiety and one of the most used drug classes in the world [63,64]. A quick solution of one mental disorder may produce another mental disorder-dependence.…”
Section: Anxiety Anxiety-related Substance Abuse or Dependence And mentioning
confidence: 99%
“…Women use psychotropic medication consistently more often compared to men and these differences also appear to be contingent on the specific mental disorder [66]. Benzodiazepine use was shown to be higher among women, in older age groups, when burdened with a severe degree of anxiety, and with decreasing income level [63][64][65][66][67].…”
Section: Anxiety Anxiety-related Substance Abuse or Dependence And mentioning
confidence: 99%
See 1 more Smart Citation